APPLICATION OF MARKETING MIX AND DIGITAL MARKETING TO SALES - Damayanti, Jessica Putri; Setyowati, Trias; Wibowo, Yohanes Gunawan (Univesitas Muhammadiyah Tangerang, 2025)
The development of the economy in the current era of globalization is very rapid and has brought major changes to high competition in all aspects of people's lives, especially in the business world that affects the way companies operate, interact, and innovate. This study aims to determine and analyze the application of marketing mix and digital marketing to sales at a souvenir shop typical of Probolinggo, tengiri brand fish crackers. This type of research uses a qualitative method by directly interviewing research respondents, namely shop owners, employees and customers. Data collection methods by conducting observations, interviews, documentation. The data analysis techniques in this study are by reducing data, presenting data, concluding and testing data validity. The results of the analysis obtained show that success in implementing marketing mix elements such as products, prices, places, and promotions has a positive impact on consumer appeal and In designing digital marketing strategies and introducing new products, Toko Oleh-Oleh utilizes internet advertising through the Instagram and WhatsApp platforms to promote its products, it has a significant impact on increasing sales